A monitoring and evaluation framework to assess the performance of innovation platforms in the context of livestock value chains - Swaans, Cornelis P.M.; Puskur, Ranjitha; Taye, H.; Girma, A. (International Livestock Research Institute, 2013)
Growing local and informal markets in Asia and Africa provide both challenges and opportunities for small holders. In developing countries, market failures often lead to suboptimal performance of the value chains and limited and inequitable participation of the poor. In recent years, innovation platforms have been promoted as mechanisms to stimulate and support multistakeholder collaboration in the context of research for development. They are recognized as having the potential to link value chain actors, and enhance communication and collaboration to overcome market failures. Despite the increased use of innovation platforms in research for development projects and programs, a monitoring and evaluation framework that encompasses the dynamic nature of innovation systems and value chains is not available. In this paper, the authors aim to develop a monitoring and evaluation framework for understanding and assessing the performance of innovation platforms in the context of pro-poor value chains, based on a discussion of various approaches.